HRM Practices and Organisational Performance - Ojochona Achimugu, Rabi; Mba Nnia SR , Ike; Kalu Emmanuel, Agbaeze; Ejikeme Emmanuel , Isichei (Review of Business Management, 2022)
Abstract Purpose – The focus of this paper was on assessing the mediating influence of strategy alignment on the link between HRM practices and organisational performance. Theoretical framework – Relevant literature provided a theoretical and empirical basis for understanding the concept through the resource based view. Design/methodology/approach – Samples were drawn from 240 employees and HR managers from selected identity management firms in Nigeria. The data analysis was carried using partial least square structural equation modelling. Findings – The study found that skill enhancing, motivational, and opportunity enhancing practices have a significant influence on organisational performance. Strategy alignment was found to mediate the relationship between HRM practices and organisational performance. Though the mediation was partial, it was significant. Practical & social implications of the research – This study highlights the need for managers to focus more on improving the HRM practices in their organisations, while also ensuring that there is an organisational strategy fit that supports HRM practices in the organisation. Originality/value – First, the paper contributes to advancing the research that captures HRM as a bundle using the varying practices in an organisation as well as to providing a vivid explanation of the role of each individual HRM practice in ensuring increased performance through strategy alignment. The study validates the resource based view as a contribution to the knowledge. Keywords - HRM Practices; Strategy Alignment; Organisational Performance; Resource Based View.